The THE ROLE OF ELECTRONIC WORD OF MOUTH (E-WOM) ON BRAND IMAGE AND ITS IMPACT ON BUYING INTEREST OF EMINA BRAND COSMETIC PRODUCTS - Arif, Mochamad; Rahmadi, Rahmadi; Alami, Febriana Indah (Sekolah Tinggi Ilmu Ekonomi Semarang, 2024)
The wider spread of the internet makes the internet a place for communication and promotion media in a business. One of the marketing strategies carried out by a company is the electronic word of mouth communication strategy which plays a role in building the brand image of a product, one of which is a product in the beauty sector. This study aims to determine the effect of electronic word of mouth on brand image and its impact on purchasing interest in Emina brand cosmetic products.The population in this study are young women aged 13-24 years in Semarang City who use social media and are users of Emina cosmetic products. The sampling technique in this study was purposive sampling with a sample size of 100 people. This research uses quantitative methods. The data obtained is analyzed then including: validity test, reliability test, classical assumption test consisting of: normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, T test, F test, and coefficient of determination (R2) analysis.The results of the data analysis carried out, the indicators used in this study are all valid and reliable. For the classical assumption test, overall the data is normally distributed. The results of the T test in this study indicate that the electronic word of mouth variable (X) has an effect on brand image (Z) with a significant value of 0.000. Brand image variable (Z) partially affects purchase intention (Y). The electronic word of mouth variable (X) partially has a positive and significant effect on purchase intention (Y) on young women who use Emina products in Semarang City, with a significant value of 0.000 less than 0.05.. The results of the coefficient of determination (R2) analysis test in this study on the electronic word of mouth (X) and brand image (Z) variables on purchase intention (Y) amounted to 52.6%.In this study, it can be concluded that (1) the electronic word of mouth variable has an influence on brand image, (2) the brand image variable has an influence on purchasing interest, (3) the electronic word of mouth variable has an influence on buying interest. For this reason, it is recommended for companies to be able to improve the brand image of products and create good marketing ideas through electronic word of mouth strategies so that purchasing interest in Emina cosmetic products increases.